2010
DOI: 10.1007/s12410-010-9057-1
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Approaches for Cardiovascular Stem Cell Imaging

Abstract: Stem cell therapies offer potential therapeutic alternatives for coronary artery disease, myocardial infarction, and heart failure. To a lesser extent, stem cell transplantations are used for experimental treatment of congenital heart conditions, atherosclerotic peripheral arterial disease, and other cardiovascular pathologies. The efficacy of stem cell transplants on the aforementioned diseases has been inconsistent, and the specific regenerative mechanisms by which stem cells work are not well understood. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In addition, for further treatment or surgery, the surgeon needs to know the position of the target tissue. To this end, various capsule‐localization techniques have been explored in feasibility studies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, for further treatment or surgery, the surgeon needs to know the position of the target tissue. To this end, various capsule‐localization techniques have been explored in feasibility studies .…”
Section: Introductionmentioning
confidence: 99%
“…Image‐based methods such as X‐ray, radionuclide labeling, and real‐time ultrasound have been used widely for object localization in biomedical applications. All of the above mentioned methods require the use of large and expensive equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Kraitchman in the current issue of your most valuable journal [1]. In their scientifically remarkable review, the authors tried to collect all available evidences on "the different imaging strategies and modalities for cell tracking, as well as the latest approaches to cell labeling in this field."…”
mentioning
confidence: 99%
“…However, I am bound to convey my experience on this issue. The authors have stated that "despite many concerns about the ionizing radiation of radionuclide tracers, none of the aforementioned studies reported any negative effects of labeling on cell viability and proliferation" [1], providing no reference for the conclusion. In my opinion, such a conclusion cannot be extended to all radionuclides.…”
mentioning
confidence: 99%
“…To the Editor: We appreciate the careful and thoughtful letter by Dr. Gholamrezanezhad regarding our recent review article about stem cell labeling and tracking in cardiovascular disease [1]. Dr. Gholamrezanezhad expresses two concerns that he feels were inadequately covered in the article.…”
mentioning
confidence: 99%